Improved dielectric and energy storage properties of polypropylene by adding hybrid fillers and high-speed extrusion. (1st February 2021) - Xie, Zilong; Liu, Dingyao; Wu, Kai; Fu, Qiang
Abstract: Polypropylene (PP) is the state-of-the-art dielectric material for film capacitor. However, the further progress of PP is impeded by its low permittivity and low energy storage density. Adding high-permittivity (high-k) nano-filler into PP matrix to prepare nanocomposites turns out to be a promising approach. Main challenge lies in the decreased electric breakdown strength (Eb ) caused by the poor filler dispersion and the contrast between the intrinsic permittivity of high-k filler and low-k polymer matrix, which generated intensified electric field to lead breakdown. Herein, this issue is addressed by the design of a hybrid filler structure, wherein both low-k high-Eb hexagonal boron nitride (h-BN) and high-k low-Eb barium titanate (BT) were uniformly incorporated in PP matrix, meanwhile high-speed extrusion technology is applied to improve the filler dispersion. As a result, an obvious increase of permittivity from 2.2 to 2.92 was achieved compared with neat PP, while the Eb of PP/BT/BN was well-maintained at 469 MV/m, bringing an increased energy density of 2.82 J cm −3 . Moreover, the dielectric loss was impressively suppressed to a low value of 0.0012 via mixing of hybrid fillers and improved dispersion. Graphical abstract: Image 1 Highlights: Introduction of high-speed extrusion to improve the filler dispersion of dielectric nanocomposites. Introduction of hybrid fillers in PP to solve the intensified electric field caused by the permittivity contrast between high-k filler and PP. Improved electric breakdown strength, dielectric constant, and energy storage density were achieved in PP/BT/BN nanocomposites.